(untitled) (The Peerian Journal, 2025)
his article presents the results of an analysis of the epizootic and epidemiological situation of anthrax in the Republic of Uzbekistan. It was noted that the dynamics of human anthrax incidence in the country, in percentage terms, directly correlates with that of animals, although the absolute number of infected animals was on average higher than that of infected humans. This indicates a direct dependence of human morbidity on the spread of infection among animals. Based on the conducted analysis, groups of regions with the highest epizootic and epidemiological potential were identified